Rekapitulasi Tanggung Jawab Keperempuanan Dalam Mengikuti Majelis Ilmu Harokah Al Iman Di Wek IV Kecamatan Padangsidimpuan Utara - Asfiati Asfiati (Jurnal Kajian Gender dan Anak, 2020)
The recapitulation of the feminine responsibilities of the congregation of Harokah al Iman shows that the existence of self-values can be obtained by following the assembly of knowledge of Harokah al Iman. This type of research is qualitative which produces descriptive data in the form of written or oral words from people and observed behavior. The primary data source is women's congregation Harokah al Iman, as many as 75 worshipers. The results showed that the responsibility of following Harokah al Iman was recapitulated by the intention of women in Wek IV in Padangsidimpuan Utara sub-district to: 1). Practicing Shari'a in the Book and Sunnah. 2). Syirik and Bid'ah, 3). Try to be able to maintain five daily prayers perfectly. 4). Trying to always do good to your neighbors, both parents. 5). Intend to pay attention to children's education. 6). Istiqomah to increase dhikr and almsgiving. The values obtained by women in following the assembly of the science of Harokah al Iman in Wek IV of Padangsidimpuan Utara District. 1). demands knowledge. 2) Hope forgiven sin, 3). Want to be happy like in a paradise garden. 4). Hoping to be shaded by angels, 5). Forgiveness, 6). Obtain a heritage of science, 7). Get peace and grace